From Monarchy to the Independent Czechoslovakia - Jirásek, Jiří (Comparative Constitutionalism in Central Europe: Analysis on Certain Central and Eastern European Countries, 2022)
During the First World War, the attitude of Czech politicians to the idea of the existence of an independent state changed fundamentally. T. G. Masaryk, who became the main representative and agent of the efforts for independence, formed, together with his associates the Czech Foreign Committee, later transformed into the Czechoslovak National Council, which sought to win over the representatives of the Entente to the idea of an independent Czech state. The Czechoslovak National Council was gradually recognized in 1918 by the individual powers of the Entente as a provisional government. The fundamental document of the domestic policy was the Declaration of the Czech Deputies of the Imperial Council and Provincial Assemblies, also called the Epiphany Declaration, adopted on 6th January 1918, demanding the independence for its nation. T. G. Masaryk responded to the manifesto of Emperor Charles I on the federalization of the Austrian part of the monarchy, an attempt to save the empire, by solemnly declaring the Czechoslovak independence, which is also known as the Washington Declaration. It already presented the form of the Czechoslovak state –republic. Czechoslovakia was established as an independent state by a revolutionary act of the Czechoslovak National Committee on 28th October 1918, which on this day declared itself the government of the new state, the executor of state power and at the same time a legislative body. Already on 13th November 1918, the National Committee promulgated a Provisional Constitution. Given its provisional nature, the Revolutionary National Assembly had the most important role, to draft and approve the fundamental law of the state. The constitutional basis of the first pre-Munich republic became the Constitutional Charter of 1920. The approval of the constitution represents the culmination of the formation of the Czechoslovak state. The adoption of the Constitutional Charter of the Czechoslovak Republic in February 1920 meant the definitive break-up of the new republic with the constitutional-legal continuity and the tradition of Austrian constitutionality. KEYWORDS: World War I, T. G. Masaryk, idea of an independent, the Washington Declaration, the Revolutionary National Assembly, the Provisional Constitution, the Constitutional Charter of the Czechoslovak Republic 1920.